2007
DOI: 10.1016/j.bbmt.2006.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Unrelated Donor Umbilical Cord Blood Transplantation versus Unrelated Donor Bone Marrow Transplantation in Adult and Pediatric Patients

Abstract: Several studies have compared the results of unrelated donor bone marrow transplantation (UBMT) and unrelated donor cord blood transplantation (UCBT). To objectively analyze these data, we performed a systematic review and meta-analysis of pooled data on comparative studies of UCBT and UBMT in patients requiring hematopoietic stem cell transplantation. Combining the studies, 161 children and 316 adults undergoing UCBT (mostly 1 or 2 antigen-mismatched), along with 316 children and 996 adults undergoing UBMT (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(96 citation statements)
references
References 35 publications
7
84
1
4
Order By: Relevance
“…[8][9][10] In addition, several registry and single institution studies have shown, both for children and adults, overall and disease-free survival rates similar to other allogeneic HSC transplants, although with different causes of mortality. [11][12][13][14][15][16][17][18] Slow and low rate of engraftment, infections during lengthy post-transplant neutropenia and toxicity of preparative regimens were recognized as factors for early TRM of CBT in large registry-based observational studies. [13][14] Low cell content in the transplanted product and higher degree of HLA incompatibility are, in turn, the main factors for graft failure and late engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] In addition, several registry and single institution studies have shown, both for children and adults, overall and disease-free survival rates similar to other allogeneic HSC transplants, although with different causes of mortality. [11][12][13][14][15][16][17][18] Slow and low rate of engraftment, infections during lengthy post-transplant neutropenia and toxicity of preparative regimens were recognized as factors for early TRM of CBT in large registry-based observational studies. [13][14] Low cell content in the transplanted product and higher degree of HLA incompatibility are, in turn, the main factors for graft failure and late engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…Cord blood is considered a treatment option in pediatric and adult patients with hematologic malignancies and disorders (leukemia, thalassemia, sickle cell disease, etc. ), bone marrow failures, inherited metabolic disorders, immunological defects and other genetic diseases [1][2][3][4][5][6][7][8][9][10][11][12]. Double umbilical cord blood grafts, that use cord blood units from two donors, mitigate cell dose limitations for larger children and adults with malignant disorders [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Recently several reviews including the clinical results of adult CBT have been published. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In this review, we focus on recent results of myeloablative CBT in adults.…”
Section: Introductionmentioning
confidence: 99%